A ventilation strategy during general anaesthesia to reduce postoperative atelectasis. (August 2014) - Edmark, Lennart; Auner, Udo; Hallén, Jan; Lassinantti-Olowsson, Lena; Hedenstierna, Göran; Enlund, Mats
Abstract Background. Atelectasis is common during and after general anaesthesia. We hypothesized that a ventilation strategy, without recruitment manoeuvres, using a combination of continuous positive airway pressure (CPAP) or positive end-expiratory pressure (PEEP) and a reduced end-expiratory oxygen fraction (FETO2) before ending mask ventilation with CPAP after extubation would reduce the area of postoperative atelectasis. Methods. Thirty patients were randomized into three groups. During induction and emergence, inspiratory oxygen fractions (FIO2) were 1.0 in the control group and 1.0 or 0.8 in the intervention groups. No CPAP/PEEP was used in the control group, whereas CPAP/PEEP of 6 cmH2O was used in the intervention groups. After extubation, FIO2 was set to 0.30 in the intervention groups and CPAP was applied, aiming at FETO2 < 0.30. Atelectasis was studied by computed tomography 25 min postoperatively. Results. The median area of atelectasis was 5.2 cm2 (range 1.6–12.2 cm2) and 8.5 cm2 (3–23.1 cm2) in the groups given FIO2 1.0 with or without CPAP/PEEP, respectively. After correction for body mass index the difference between medians (2.9 cm2) was statistically significant (confidence interval 0.2–7.6 cm2, p = 0.04). In the group given FIO2 0.8, in which seven patients were ex- or current smokers, the median area of atelectasis was 8.2 cm2 (1.8–14.7 cm2). Conclusion. Compared with conventional ventilation, after correction for obesity, this ventilation strategy reduced the area of postoperative atelectasis in one of the intervention groups but not in the other group, which included a higher proportion of smokers.